Chemical contaminants entering food products from polymer packaging. Review - D. A. Utyanov; N. L. Vostrikova; E. R. Vasilevskaya; A. V. Kulikovskii; S. Yu. Karabanov (Пищевые системы, 2025)
The paper presents a review of scientific literature devoted to the problem of food product contamination with various types of substances from packaging materials. The problem under consideration is large-scale — there are many types of compounds that can enter food products from packaging. Food product contamination can occur due to migration of substances used for production of packaging materials. Plastic polymer packages represent the highest risk of food product contamination. The interest of the scientific community and the need for studying the described theme are determined by the fact that the prevailing proportion of all compounds that migrate into a food product from packaging possesses toxic or carcinogenic activity, and thus, presents the potential risk for human health. Bisphenols are most studied among all contaminants described in this paper. Many studies on their migration into food products have shown that bisphenols were found practically in all types of food products: meat, dairy, fish, fruit and vegetable. The significant migration of bisphenols has been observed in juice products and bottled water. Due to the adverse effect of bisphenol A on the human body, its use in the production of packaging materials for food products is forbidden. However, this ban has led to distribution of analogs, namely, bisphenols B, C, F, AF and others, which are found in food products. The performed review has shown that the problem of food product contamination with contaminants from packaging materials requires serious attention of the scientific community.